Supported catalyst as well as preparation method and application thereof
Through a method of preparing a supported catalyst, the problem of existing platinum-based catalysts aggregation and poor durability in electrocatalytic oxygen reduction reactions is solved, efficient utilization and distribution uniformity of precious metals are achieved, and the durability and electrical properties of the catalyst are enhanced. Catalytic activity.
Patent Information
- Application Number
- CN202510061960.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-15
AI Technical Summary
Existing platinum-based catalysts are prone to aggregation in electrocatalytic oxygen reduction reactions, resulting in a reduced utilization rate, poor durability, high cost, complex and lengthy preparation process, and large amount of precious metals.
By a method of preparing a supported catalyst, it includes precipitation reaction of vanadate and ammonium salt in a solvent to form a carrier precursor, then reacting with noble metal compounds, chelating agents and reducing agents in another solvent, and finally Annealing is performed in the protective gas to produce a supported catalyst.
The utilization rate and distribution uniformity of precious metals in the supported catalyst are improved, the migration and aggregation of precious metals are reduced, the durability and electrocatalytic activity of the catalyst are enhanced, the preparation process is simplified, and the cost is reduced.
Smart Images

Figure CN119481118A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to a supported catalyst, a preparation method and application thereof. Background Art
[0002] Currently, platinum-based catalysts (such as commercial Pt / C) are common oxygen reduction reaction electrocatalysts. However, Pt particles are prone to aggregation during the electrocatalytic oxygen reduction reaction (ORR), which leads to a reduction in the exposed area of the Pt particles and a decrease in utilization. In addition, Pt / C has poor durability, high price, and limited Pt reserves. Therefore, there is an urgent need to reduce the amount of Pt used while improving its durability and electrocatalytic activity.
[0003] At present, the methods to improve its durability include element doping and carrier structure confinement. Among them, element doping includes nitrogen doping, and the doping methods include: in-situ synthesis method and post-treatment method. Among them, the former directly nitrides the carrier carbon with nitrogen-rich substances as precursors, while the latter first synthesizes the carbon material precursor and then performs surface modification on the carbon precursor with a reagent containing nitrogen atoms. Doping with nitrogen elements can enhance the surface polarity of the carrier carbon material, improve the surface wettability, reduce the ion adsorption and desorption energy barrier, and modify the surface electronic structure of carbon atoms, thereby improving the adsorption performance of the carbon carrier and the durability of the catalyst. However, both of the above methods are to mix the noble metal ion solution and the precipitant to form a precipitate, and then immerse and adsorb it on the surface of the carrier doped with nitrogen, and then filter, wash and dry it, and finally obtain a platinum-based catalyst; the catalyst prepared by this method has a weak interaction between the active metal particles and the carrier, which will cause the active metal particles to migrate and agglomerate, and the active metal particles are easily embedded in the pore structure of the carrier, and the active metal particles are wrapped, which makes it difficult for the active metal particles to effectively contact the reactants during the catalytic reaction, and the atomic utilization rate of the active metal particles at the interface is low. Based on the above analysis, the existing methods have the problems of lengthy preparation process, large amount of noble metals, high cost, and easy migration, aggregation and poor durability of the noble metals in the prepared platinum-based catalyst.
[0004] Carbon materials have large specific surface area, high porosity, good electrical conductivity, excellent chemical stability and corrosion resistance and have become one of the most commonly used supports for supported catalysts. Metal-nitrogen-carbon (MNC) is a strong competitor to reduce or replace precious metal Pt-based catalysts; the sp 2 The hybrid structure has a delocalized π orbital and exhibits good conductivity. In addition, in the MNC structure, the N atom has a stronger electronegativity than the C atom, which can cause electrons to gather around the N atom, thereby reducing the electron cloud density near the C atom and promoting the O 2The adsorption of molecules accelerates the process of oxygen reduction reaction (ORR). Non-precious metal oxides, nitrides, sulfides, selenides, phosphides, etc. have been studied to improve the reaction kinetics of ORR; among them, transition metal nitrides, through the introduction of nitrogen atoms, change the electron cloud state density at the center of the parent metal d band, so that the electronic structure of transition metal nitrides is similar to that of precious metals (Pd and Pt), and have excellent electrocatalytic activity and durability. For example, vanadium nitride (VN) has electronic properties similar to Pt; however, the electrocatalytic performance of VN is restricted by factors such as insufficient exposure of electronic configuration and active sites, which leads to the improvement of its electrocatalytic performance. In addition, the preparation methods of vanadium nitride (VN) can be specifically divided into physical and chemical methods. The physical method mainly includes physical vapor deposition and pulsed laser deposition, because it requires high pressure or high temperature equipment; and it is not easy to control the morphology and structure of VN during the preparation reaction. The chemical method is to use vanadium-containing precursors and nitrogen-containing substances to react chemically under certain conditions to generate VN. Among them, the vanadium-containing precursors mainly include vanadium oxides, sulfides, chlorides and vanadates, and the nitrogen-containing substances mainly include NH 3 、N 2 and nitrogen-containing organic matter, etc. However, this process is difficult to achieve coordinated regulation of VN structure and morphology, and the prepared VN is severely agglomerated, has a small specific surface area, and low purity, which leads to problems such as insufficient durability and poor activity of the catalyst with VN as the carrier.
[0005] Therefore, it is necessary to research and develop a supported catalyst with simple preparation process, low cost, non-easy migration and aggregation of precious metals, long-lasting durability and high activity, which is of great significance for improving the activity and durability of the electrocatalyst of the cathode oxygen reduction reaction of hydrogen fuel cells. Summary of the invention
[0006] The main purpose of the present invention is to provide a supported catalyst, a preparation method and application thereof, so as to solve the problems in the prior art that the preparation process of supported catalysts is complicated and lengthy, the amount of precious metals used is large, and the precious metals in the prepared catalysts are easy to migrate and aggregate and have poor durability and activity.
[0007] In order to achieve the above-mentioned purpose, the present invention provides a method for preparing a supported catalyst on one hand, which comprises: step S1, allowing a vanadate and a first ammonium salt to undergo a precipitation reaction in a first solvent to obtain a first product system containing a support precursor; step S2, allowing a support precursor, a second ammonium salt, a noble metal compound, a chelating agent, and a first reducing agent to react in a second solvent to obtain a second product system containing a catalyst precursor; step S3, annealing the catalyst precursor and the second reducing agent in a protective gas to obtain a supported catalyst.
[0008] Furthermore, the weight ratio of the vanadate, the first ammonium salt and the first solvent is (1-30):(0.01-10):(100-1500).
[0009] Further, the vanadate is selected from one or more of the group consisting of sodium vanadate, potassium vanadate, calcium vanadate, sodium pyrovanadate, potassium pyrovanadate, calcium pyrovanadate, sodium metavanadate, potassium metavanadate and calcium metavanadate.
[0010] Further, the first ammonium salt is selected from one or more of the group consisting of ammonium chloride, ammonium sulfate, ammonium bisulfate, ammonium bicarbonate, ammonium carbonate, polydopamine, hexamethylenetetramine, melamine, ammonium polyacrylate and dopamine hydrochloride.
[0011] Furthermore, the first solvent is a mixture of water and an organic solvent, and the organic solvent is selected from one or more of the group consisting of methanol, ethanol, propanol, ethylene glycol, isopropanol, polyacrylic acid, N,N-dimethylformamide, N,N-dimethylacetamide and diethylformamide; preferably, the first solvent is a mixture of water and an organic solvent in a volume ratio of (50 to 1000): (5 to 500).
[0012] Furthermore, step S1 includes: step S1-1, mixing the vanadate-containing raw material with water to obtain a mixed system, using alkali solution to adjust the pH of the mixed system to 7.5-10.5 to remove impurities, and obtaining a purified mother liquor containing vanadate; step S1-2, mixing the first ammonium salt with the first solvent to obtain an ammonium salt solution; step S1-3, mixing the purified mother liquor with the ammonium salt solution and performing a precipitation reaction to obtain a first product system.
[0013] Further, the alkali solution is selected from NaOH aqueous solution, Na 2 CO 3 Aqueous solution, NaHCO 3 Aqueous solution, KOH aqueous solution, K 2 CO 3 Aqueous solution, KHCO 3 One or more of the group consisting of aqueous solution and sodium acetate aqueous solution, preferably the mass concentration of the alkali solution is 5.0-100.0 g / L.
[0014] Furthermore, in step S1-1, the mixing temperature is 10 to 95°C, the mixing time is 5 to 180 min, and stirring is preferably performed during the mixing process, and the stirring speed is preferably 300 to 500 rpm.
[0015] Furthermore, the mass concentration of the ammonium salt solution is 5.0 to 100.0 g / L.
[0016] Furthermore, in step S1-3, the ammonium salt solution is dripped into the purified mother liquor; preferably, the dripping rate is 1 to 30 mL / min.
[0017] Furthermore, the volume ratio of the purified mother liquor to the ammonium salt solution is (2-5):1.
[0018] Furthermore, the precipitation reaction temperature is 20 to 80° C., and the time is 10 to 60 minutes.
[0019] Furthermore, the preparation method further comprises: sequentially performing solid-liquid separation and drying on the first product system to obtain a carrier precursor.
[0020] Furthermore, solid-liquid separation is selected from centrifugal separation.
[0021] Furthermore, the drying temperature is 50 to 90° C., and the drying time is 6 to 24 hours.
[0022] Furthermore, the weight ratio of the carrier precursor to the noble metal-containing compound is (1-20): (0.1-10).
[0023] Furthermore, the weight ratio of the noble metal compound to the chelating agent is (0.1-10): (0.001-15).
[0024] Furthermore, the molar ratio of the noble metal-containing compound to the first reducing agent is (0.001-0.1): (0.005-0.5).
[0025] Furthermore, the noble metal-containing compound is a platinum salt compound, preferably chloroplatinic acid, chloroplatinate, [Pt(acac) 2 ], platinum diamine dinitrite and [Pt(CH 3 NH 2 ) 4 ][PtCl 4 ]One or more of the group consisting of ].
[0026] Further, the chelating agent is selected from one or more of the group consisting of thiourea, sulfite, phosphoric acid, oxalic acid, arsenic acid, polyacrylic acid and polyvinyl alcohol.
[0027] Further, the first reducing agent is selected from one or more of the group consisting of elemental sulfur, ascorbic acid, sodium ascorbate, sodium citrate, formaldehyde, acetaldehyde, formic acid, acetic acid, hydrazine hydrate, metal borohydride salts, sulfites, ammonium chloride and oleylamine.
[0028] Furthermore, the second solvent is selected from water and / or ethylene glycol.
[0029] Furthermore, step S2 includes: step S2-1, mixing the carrier precursor, the second ammonium salt, the precious metal compound, the chelating agent and the third solvent to obtain a first mixed liquid; step S2-2, mixing the first reducing agent, the dispersant and the fourth solvent to obtain a second mixed liquid; step S2-3, mixing the first mixed liquid and the second mixed liquid and reacting them to obtain a second product system.
[0030] Furthermore, the weight ratio of the carrier precursor, the noble metal-containing compound and the third solvent is (1-20): (0.1-10): (100-5000).
[0031] Furthermore, the weight ratio of the carrier precursor to the second ammonium salt is (1-20): (0.001-15).
[0032] Further, the second ammonium salt is selected from one or more of the group consisting of ammonium chloride, ammonium sulfate, ammonium bisulfate, ammonium bicarbonate, ammonium carbonate, polydopamine, ethylenediaminetetraacetic acid, ethylenediamine, triethylenetetramine, triethanolamine, hexamethylenetetramine, melamine, ammonium polyacrylate and dopamine hydrochloride.
[0033] Furthermore, the second ammonium salt is of the same type as the first ammonium salt.
[0034] Further, the third solvent is selected from water and / or ethylene glycol.
[0035] Further, the fourth solvent is selected from one or more of the group consisting of water, methanol, ethanol, propanol, ethylene glycol, isopropanol, N,N-dimethylformamide, N,N-dimethylacetamide and diethylformamide.
[0036] Furthermore, in step S2-1, the mixing temperature is 0 to 150°C and the mixing time is 30 to 180 minutes.
[0037] Furthermore, in step S2-2, the molar concentration of the first reducing agent in the second mixed solution is 0.01 to 10 mol / L.
[0038] Furthermore, in step S2-3, the first mixed solution is dripped into the second mixed solution at a rate of 1 to 10 mL / min, and the mixing is preferably carried out under stirring conditions, and the stirring speed is preferably 300 to 500 rpm; the reaction time is preferably 10 to 60 min.
[0039] Furthermore, a dispersant is added in step S2-3.
[0040] Furthermore, in the second mixed liquid, the mass concentration of the dispersant is 1.0 to 5.0 g / L.
[0041] Further, the dispersant is selected from one or more of the group consisting of polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone, methyl cellulose, polyacrylic acid, sodium sulfosuccinate, sodium lauryl sulfate, sodium citrate and quaternary ammonium salts.
[0042] Furthermore, the preparation method further comprises: sequentially performing solid-liquid separation and freeze-drying treatment on the second product system to obtain a catalyst precursor.
[0043] Furthermore, the solid-liquid separation is selected from centrifugal separation.
[0044] Furthermore, the freeze-drying treatment is performed at a temperature of -10°C to -60°C and a time of 6 to 24 hours.
[0045] Further, the annealing treatment includes staged temperature rising treatment, including a first stage heat treatment, a second stage heat treatment, a third stage heat treatment and a fourth stage heat treatment performed in sequence.
[0046] Furthermore, the first stage heat treatment includes: heating from 25°C to 300-350°C at a heating rate of 5-30°C / min, and keeping warm for 1-1.5 hours; the second stage heat treatment includes: continuing to heat up to 600-650°C at a heating rate of 5-10°C / min, and keeping warm for 1-3 hours; the third stage heat treatment includes: continuing to heat up to 800-900°C at a heating rate of 5-10°C / min, and keeping warm for 1-3 hours; the fourth stage heat treatment includes: continuing to heat up to 1100-1200°C at a heating rate of 5-10°C / min, and keeping warm for 1-3 hours.
[0047] Furthermore, the protective gas includes argon, nitrogen, helium and NH 3 One or more of the groups.
[0048] Furthermore, the second reducing agent is elemental carbon; further preferably, the weight ratio of the second reducing agent to the catalyst precursor is (0.1-0.5):1; preferably, the average particle size of the second reducing agent is 50-1000 nm.
[0049] Furthermore, the annealing treatment is carried out in a tubular vacuum furnace, and the volume flow rate of the protective gas is 1 to 10 L / min.
[0050] Furthermore, the preparation method further comprises: grinding the thermal reduction product after the annealing treatment to obtain a supported catalyst.
[0051] In order to achieve the above object, another aspect of the present invention further provides a supported catalyst, which includes a carrier and a noble metal; the supported catalyst is prepared by the preparation method of the supported catalyst provided in the present application.
[0052] Furthermore, in the supported catalyst, the loading amount of the noble metal is 20 to 40 wt %.
[0053] Furthermore, the pore volume of the supported catalyst is 0.01 to 10.0 cm 3 / g, average pore size of 5-50nm, specific surface area of 450-600m 2 / g.
[0054] Another aspect of the present invention provides a hydrogen fuel cell, comprising a catalyst, wherein the catalyst comprises the above-mentioned supported catalyst provided in the present application.
[0055] By applying the technical solution of the present invention, compared with the traditional deposition reduction method of first preparing a vanadium nitride (VN) carrier and then immersing it in a platinum salt compound solution for loading elemental platinum particles, the present application can deposit atomic platinum in situ on the surface of the carrier precursor during the reduction of the precious metal compound, which can not only improve the utilization rate of the active component (i.e., the precious metal Pt) in the supported catalyst, but also improve the distribution uniformity of the precious metal on the support surface, and the precious metal in the supported catalyst prepared by this method is not easy to migrate and aggregate, and can achieve the regulation of the interaction between the precious metal and the carrier in the supported catalyst, so that the interaction between the precious metal and the carrier is stronger, and the precious metal can be effectively anchored, so that the durability of the prepared supported catalyst is better. Moreover, the above-mentioned preparation method of the present application requires less precious metal and higher atomic utilization. In addition, compared with the traditional impregnation deposition reduction method, the above-mentioned preparation method provided by the present application can well retain its morphology while changing the composition structure of the supported catalyst, so that it exposes more active sites.
[0056] During the annealing of the catalyst precursor, NH 3 On the one hand, the release of gas can form a porous structure, which can play a role in expanding the pores and increasing the specific surface area of the carrier, so that the supported catalyst can expose more catalytic active sites. Its application in hydrogen fuel cells can significantly improve the transport of reactants and products during the cathode oxygen reduction reaction and enhance mass transfer; on the other hand, under the action of the local micro-jet flow in the capillary pores of the carrier interface, the interaction energy between the precious metal particles is weakened, thereby effectively inhibiting the aggregation and migration of the precious metal particles.
[0057] In addition, the supported catalysts prepared by the phase separation method assisted by precious metal chelates have the following advantages: (1) Due to the good interaction between Pt and VN, the electronic structure at the coupling interface can be adjusted; (2) Reducing the particle size can provide more active sites; (3) The unique porous network of the VN support can not only improve the structural integrity and electrochemical durability, but also provide ultrafast electron / ion transfer channels. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0059] Figure 1 The transmission electron microscope image (TEM image) of the supported catalyst prepared in Example 1 is shown;
[0060] Figure 2 The transmission electron microscope image (TEM image) of the supported catalyst prepared in Example 1 is shown;
[0061] Figure 3 shows the nitrogen adsorption-desorption curve of the supported catalyst prepared in Example 1;
[0062] Figure 4 The pore size distribution diagram of the supported catalyst prepared in Example 1 is shown;
[0063] Figure 5 The cyclic voltammetry curve (CV diagram) of the supported catalyst prepared in Example 1 is shown;
[0064] Figure 6 The linear sweep voltammetry curve (LSV diagram) of the supported catalyst prepared in Example 1 is shown. DETAILED DESCRIPTION
[0065] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0066] As described in the background technology, the existing supported catalysts have the problems of complex preparation process, large amount of precious metals, easy migration and aggregation of precious metals in the prepared catalysts, poor durability and poor activity. In order to solve the above technical problems, the first aspect of the present application provides a method for preparing a supported catalyst, which comprises: step S1, causing vanadate and a first ammonium salt to undergo precipitation reaction in a first solvent to obtain a first product system containing a support precursor; step S2, causing a support precursor, a second ammonium salt, a precious metal compound, a chelating agent, and a first reducing agent to react in a second solvent to obtain a second product system containing a catalyst precursor; step S3, annealing the catalyst precursor and the second reducing agent in a protective gas to obtain a supported catalyst.
[0067] In step S1, the vanadate reacts with the first ammonium salt to produce ammonium metavanadate (NH 4 VO 3 ), while the excess vanadate that did not participate in the precipitation reaction was hydrated to give [VO 2 (H2 O) 3 ] + , which is deprotonated to generate VO(OH) 3 , to obtain NH 4 VO 3 and a small amount of VO(OH) 3 The following reactions occur during this process: . Due to NH 4 VO 3 The solubility in water is very low, so the following double decomposition reaction occurs: (1) ; (2) .
[0068] Step S2 uses a metallurgical hydrometallurgical process to efficiently enrich platinum, form a precious metal precipitate compound that is difficult to ionize through double decomposition reaction and phase transformation, and impregnate, adsorb and deposit it on the surface of the carrier precursor to form a catalyst precursor. The following reactions occur in this process:
[0069] When the second ammonium salt is ammonium chloride and the noble metal-containing compound is chloroplatinic acid: ;
[0070] When the chelating agent is oxalic acid, platinum salt (NH 4 ) 2 PtCl 6 The phase transformation produces ammonium chloroplatinate (NH 4 ) 2 PtCl 4 (Ammonium chloroplatinite is easily soluble in water), and the following reaction occurs: ;
[0071] And under the action of weak reducing agent hydrogen peroxide and / or hydrazine hydrate, the following reaction is carried out:
[0072] ;
[0073] .
[0074] Moreover, the introduction of the chelating agent in step S2 can enable the noble metal to form a noble metal chelate with the chelating agent, so that the noble metal is dispersed more evenly in the second solvent under the action of the steric hindrance of the chelating agent, that is, the concentration of the noble metal ions can be regulated through the noble metal cation chelate effect, so that the growth rate of the nanocrystal nucleus is slowed down, allowing the nano Pt grains to be deposited in situ with a smaller volume, thereby enabling the reaction in the system to proceed more stably and improving the distribution uniformity of the noble metal in the carrier precursor.
[0075] In step S3, under a protective atmosphere, 4VO 3 The V and N atoms in the polymer are converted into VN small particles in situ, while the carbon in the precious metal chelate framework and the added second reducing agent (such as elemental carbon) are consumed to promote the reduction of elemental Pt. Since the atoms in the polymer act as dispersants and protective agents, the phase separation is ensured while the particles do not agglomerate and grow. At the same time, the ammonium metavanadate in step S3 is thermally decomposed to obtain vanadium pentoxide (V 2 O 5 ) and ammonia (NH 3 ), while VO(OH) 3 Dehydration to form V 2 O 5 , V 2 O 5 It is reduced by the second reducing agent to form vanadium nitride (VN), that is, the following reaction occurs:
[0076] , , ;
[0077] Thus, a supported catalyst is formed in which the noble metal is supported by vanadium nitride.
[0078] The following reactions occur during this process:
[0079] ;
[0080] .
[0081] Compared with the traditional deposition reduction method of first preparing a vanadium nitride (VN) carrier and then immersing it in a platinum salt compound solution for elemental platinum loading, the present application can be deposited in situ on the surface of the carrier precursor during the reduction of the precious metal compound, which can not only improve the utilization rate of the active component (ie, the precious metal Pt) in the supported catalyst, but also improve the distribution uniformity of the precious metal on the support surface. The precious metal in the supported catalyst prepared by this method is not easy to migrate and aggregate, and the interaction between the precious metal and the carrier in the supported catalyst can be regulated, so that the interaction between the precious metal and the carrier is stronger, and the precious metal can be effectively anchored, so that the durability of the prepared supported catalyst is better. Moreover, the above-mentioned preparation method of the present application requires less precious metal and higher atomic utilization. In addition, compared with the traditional impregnation deposition reduction method, the above-mentioned preparation method provided by the present application can well retain its morphology while changing the composition structure of the supported catalyst, so that it exposes more active sites.
[0082] During the annealing of the catalyst precursor, NH 3On the one hand, the release of gas can form a porous structure, which can play a role in expanding the pores and increasing the specific surface area of the carrier, so that the supported catalyst can expose more catalytic active sites. Its application in hydrogen fuel cells can significantly improve the transport of reactants and products during the cathode oxygen reduction reaction and enhance mass transfer; on the other hand, under the action of the local micro-jet flow in the capillary pores of the carrier interface, the interaction energy between the precious metal particles is weakened, thereby effectively inhibiting the aggregation and migration of the precious metal particles.
[0083] In addition, the supported catalysts prepared by the phase separation method assisted by precious metal chelates have the following advantages: (1) Due to the good interaction between Pt and VN, the electronic structure at the coupling interface can be adjusted; (2) Reducing the particle size can provide more active sites; (3) The unique porous network of the VN support can not only improve the structural integrity and electrochemical durability, but also provide ultrafast electron / ion transfer channels.
[0084] In a preferred embodiment, the weight ratio of the vanadate, the first ammonium salt and the first solvent is (1-30): (0.01-10): (100-1500). The weight ratio of the vanadate, the first ammonium salt and the first solvent includes but is not limited to the above range. Limiting it to the above range is conducive to improving the utilization rate of raw materials and the production rate of ammonium metavanadate, thereby facilitating the subsequent formation of a catalyst precursor.
[0085] In order to provide a source of vanadium element and reduce the introduction of impurity elements, preferably, the vanadate includes but is not limited to one or more of the group consisting of sodium vanadate, potassium vanadate, calcium vanadate, sodium pyrovanadate, potassium pyrovanadate, calcium pyrovanadate, sodium metavanadate, potassium metavanadate and calcium metavanadate.
[0086] In order to react with vanadate to precipitate and facilitate the subsequent thermal decomposition of the catalyst precursor to obtain V 2 O 5 Preferably, the first ammonium salt includes but is not limited to one or more of the group consisting of ammonium chloride, ammonium sulfate, ammonium bisulfate, ammonium bicarbonate, ammonium carbonate, polydopamine, hexamethylenetetramine, melamine, ammonium polyacrylate and dopamine hydrochloride.
[0087] In a preferred embodiment, the first solvent includes but is not limited to a mixture of water and an organic solvent, and the organic solvent includes but is not limited to one or more of the group consisting of methanol, ethanol, propanol, ethylene glycol, isopropanol, polyacrylic acid, N,N-dimethylformamide, N,N-dimethylacetamide and diethylformamide. Compared with other types, the use of the above-mentioned first solvent is conducive to improving the dispersibility of vanadate and ammonium salt, thereby facilitating the precipitation reaction between the two.
[0088] In order to further improve the dispersibility of vanadate and ammonium salt, preferably, the first solvent is a mixture of water and an organic solvent in a volume ratio of (50-1000):(5-500).
[0089] In a preferred embodiment, step S1 includes: step S1-1, mixing the vanadate-containing raw material with water to obtain a mixed system, using alkali solution to adjust the pH of the mixed system to 7.5-10.5 to remove impurities, and obtaining a purified mother liquor containing vanadate; step S1-2, mixing the first ammonium salt with the first solvent to obtain an ammonium salt solution; step S1-3, mixing the purified mother liquor with the ammonium salt solution and performing a precipitation reaction to obtain a first product system. Utilizing the difference in the solubility product of the impurity elements, using alkali solution to adjust the pH value of the mixed system within the above range is conducive to purifying and removing impurities from the vanadate-containing raw material, improving the purity of the vanadate, and obtaining a purified mother liquor containing vanadate; mixing the purified mother liquor obtained after purification and impurity removal with the ammonium salt solution and performing a precipitation reaction is conducive to improving the purity of the carrier precursor. Moreover, the surface of the carrier precursor prepared by the above method is adsorbed with water molecules, which is conducive to improving its wettability, facilitating subsequent subsequent treatment and facilitating the loading of precious metals on the carrier surface, thereby omitting the carrier pretreatment process, making the process more concise, efficient, lower energy consumption, and more significant cost advantages.
[0090] In order to further improve the removal rate of impurities and further reduce the cost of impurity removal, preferably, the alkali solution includes but is not limited to NaOH aqueous solution, Na 2 CO 3 Aqueous solution, NaHCO 3 Aqueous solution, KOH aqueous solution, K 2 CO 3 Aqueous solution, KHCO 3 One or more of the group consisting of aqueous solution and sodium acetate aqueous solution.
[0091] In order to further improve the removal rate of impurities, preferably, the mass concentration of the alkali solution is 5.0-100.0 g / L.
[0092] In a preferred embodiment, the mixing temperature in step S1-1 is 10-95°C and the mixing time is 5-180 min. The mixing temperature and time in this step include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the solubility and dispersibility of the vanadate-containing raw material in the mixed system, thereby facilitating subsequent processing.
[0093] In order to further improve the solubility and dispersibility of the vanadate-containing raw material in the mixed system, preferably, stirring is performed during the mixing process in step S1-1, and the stirring speed is preferably 300 to 500 rpm.
[0094] In a preferred embodiment, the mass concentration of the ammonium salt solution is 5.0 to 100.0 g / L. The mass concentration of the ammonium salt solution includes but is not limited to the above range. Limiting it to the above range is beneficial to the utilization rate of the raw materials of the ammonium salt, while improving the reaction efficiency of the precipitation reaction and increasing the precipitation reaction product (containing NH 4 VO 3 and a small amount of VO(OH) 3 The yield of the carrier precursor).
[0095] In order to better control the precipitation reaction rate, preferably, in step S1-3, an ammonium salt solution is dripped into the purified mother liquor. In order to further control the precipitation reaction rate, the formed NH 4 VO 3 The structure is more stable. Preferably, the dripping rate is 1 to 30 mL / min.
[0096] In a preferred embodiment, the volume ratio of the purified mother liquor containing vanadate to the ammonium salt solution is (2-5):1. The volume ratio of the purified mother liquor containing vanadate to the ammonium salt solution includes but is not limited to the above range, and limiting it to the above range is beneficial to increase NH 4 VO 3 The yield is good, which facilitates the subsequent preparation of the catalyst precursor.
[0097] In order to make the precipitation reaction proceed more thoroughly, preferably, the precipitation reaction temperature is 20 to 80° C. and the time is 10 to 60 minutes.
[0098] In a preferred embodiment, the preparation method provided by the present application further comprises: sequentially performing solid-liquid separation and drying on the first product system to obtain a carrier precursor. Performing solid-liquid separation on the first product system is beneficial for separating the carrier precursor from the first solvent to obtain a solid phase product, and drying the solid phase product is beneficial for removing the residual solvent entrained in the solid phase product, which is convenient for subsequent processing.
[0099] In order to improve the separation efficiency of the carrier precursor and the first solvent, preferably, the solid-liquid separation includes but is not limited to centrifugal separation.
[0100] In order to improve the removal rate of residual solvent entrained in the solid phase product, preferably, the drying temperature is 50 to 90° C. and the drying time is 6 to 24 hours.
[0101] In a preferred embodiment, the weight ratio of the carrier precursor to the noble metal compound is (1-20): (0.1-10). The weight ratio of the carrier precursor to the noble metal compound includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the utilization rate of the noble metal and reducing the amount of the noble metal.
[0102] In a preferred embodiment, the weight ratio of the noble metal compound to the chelating agent is (0.1-10): (0.001-15). The weight ratio of the noble metal compound to the chelating agent includes but is not limited to the above range. Limiting it within the above range is conducive to improving the dispersibility of the noble metal compound, thereby improving the uniformity of the distribution of the noble metal in the catalyst precursor on the surface of the carrier precursor, and facilitating the subsequent inhibition of agglomeration and migration of the noble metal in the supported catalyst.
[0103] In order to improve the reaction efficiency, preferably, the molar ratio of the noble metal-containing compound to the first reducing agent is (0.001-0.1): (0.005-0.5).
[0104] In order to improve the dispersibility of the noble metal compound in the second solvent, it is convenient to obtain platinum metal particles after the reaction so as to exert its catalytic effect. At the same time, in order to improve the catalytic efficiency of the supported catalyst, preferably, the noble metal compound is a platinum salt compound, preferably chloroplatinic acid, chloroplatinate, [Pt(acac) 2 ], platinum diamine dinitrite and [Pt(CH 3 NH 2 ) 4 ][PtCl 4 ]One or more of the group consisting of ].
[0105] In a preferred embodiment, the chelating agent includes, but is not limited to, one or more of the group consisting of thiourea, sulfite, phosphoric acid, oxalic acid, arsenic acid, polyacrylic acid and polyvinyl alcohol. Compared with other types, the use of the above-mentioned types of chelating agents is conducive to improving the dispersibility of the noble metal compound in the second solvent, facilitating the acquisition of platinum metal single substance particles after the reaction, thereby exerting its catalytic effect.
[0106] In a preferred embodiment, the first reducing agent includes, but is not limited to, one or more of the group consisting of elemental sulfur, ascorbic acid, sodium ascorbate, sodium citrate, hydrogen peroxide, formaldehyde, acetaldehyde, formic acid, acetic acid, hydrazine hydrate, metal borohydride salts, sulfites, ammonium chloride and oleylamine. Compared with other types, the use of the above-mentioned first reducing agents is conducive to improving the reaction efficiency.
[0107] In order to improve the dispersibility of each material, preferably, the second solvent includes but is not limited to water and / or ethylene glycol.
[0108] In a preferred embodiment, step S2 includes: step S2-1, mixing a carrier precursor, a second ammonium salt, a noble metal compound, a chelating agent and a third solvent to obtain a first mixed solution; step S2-2, mixing a first reducing agent, a dispersant and a fourth solvent to obtain a second mixed solution; step S2-3, mixing the first mixed solution and the second mixed solution and reacting to obtain a second product system. The use of a mixed solution of water and / or ethylene glycol in the first mixed solution is beneficial to improving the wettability of the carrier precursor and improving the loading effect of the noble metal particles. Moreover, the preparation of the second product system using the above-mentioned preparation process is beneficial to improving the dispersibility of each reaction raw material in the solvent, and is beneficial to improving the raw material utilization rate of each reaction raw material. At the same time, it is also beneficial for the reaction to proceed more smoothly, thereby improving the yield of the catalyst precursor and the uniformity of the distribution of the noble metal in the catalyst precursor.
[0109] In order to make the amount of precious metal in the subsequently prepared supported catalyst more appropriate and improve the catalytic activity of the supported catalyst, preferably, the weight ratio of the support precursor, the precious metal-containing compound and the third solvent is (1-20): (0.1-10): (100-5000).
[0110] In order to improve the effect of phase conversion of platinum salt and formation of noble metal chelate, preferably, the weight ratio of the carrier precursor to the second ammonium salt is (1-20): (0.001-15).
[0111] In order to improve the effect of phase transformation of platinum salt and generating precious metal chelate, preferably, the second ammonium salt includes but is not limited to one or more of the group consisting of ammonium chloride, ammonium sulfate, ammonium bisulfate, ammonium bicarbonate, ammonium carbonate, polydopamine, ethylenediaminetetraacetic acid, ethylenediamine, triethylenetetramine, triethanolamine, hexamethylenetetramine, melamine, ammonium polyacrylate and dopamine hydrochloride.
[0112] In a preferred embodiment, the second ammonium salt is of the same type as the first ammonium salt.
[0113] In order to improve the dispersibility of each raw material in the third solvent, preferably, the third solvent includes but is not limited to water and / or ethylene glycol.
[0114] In order to improve the dispersibility of each raw material in the fourth solvent, preferably, the fourth solvent includes but is not limited to one or more of the group consisting of water, methanol, ethanol, propanol, ethylene glycol, isopropanol, N,N-dimethylformamide, N,N-dimethylacetamide and diethylformamide. When the fourth solvent includes the above-mentioned types of organic solvents, the functional groups of the organic solvent replace the non-bridging hydroxyl groups on the surface of the carrier precursor, and play a certain steric hindrance role to inhibit the agglomeration of the carrier precursor, and is conducive to controlling the nucleation rate of the noble metal and the size of the noble metal particles; moreover, the organic solvent has a lower surface tension than water, which is convenient for subsequent annealing treatment.
[0115] In a preferred embodiment, in step S2-1, the mixing temperature is 0 to 150° C. and the mixing time is 30 to 180 min. The mixing temperature and time include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the dispersibility of the carrier precursor, the noble metal compound and the chelating agent in the second solvent, which is convenient for subsequent reactions.
[0116] In a preferred embodiment, in step S2-2, the molar concentration of the first reducing agent in the second mixed solution is 0.01 to 10 mol / L. The molar concentration of the first reducing agent includes but is not limited to the above range, and limiting it within the above range is conducive to improving the reaction efficiency, thereby facilitating the improvement of the yield of the zero-valent noble metal and the catalytic activity of the supported catalyst.
[0117] In a preferred embodiment, in step S2-3, the first mixed solution is dripped into the second mixed solution at a rate of 1-10 mL / min. Mixing the first mixed solution with the second mixed solution in the above manner is beneficial to improving the reaction efficiency and thus the yield of the zero-valent noble metal.
[0118] In order to further improve the reaction efficiency and the yield of zero-valent noble metals, preferably, the mixing in step S2-3 is performed under stirring conditions, and the stirring speed is 300 to 500 rpm.
[0119] In order to further improve the reaction efficiency and the yield of the zero-valent noble metal, preferably, the reaction time is 10 to 60 minutes.
[0120] In order to further improve the dispersibility and compatibility of the raw materials during the reaction, preferably, in the second mixed solution, the mass concentration of the dispersant is 1.0 to 5.0 g / L.
[0121] In order to further improve the dispersibility and compatibility of the raw materials during the reaction, preferably, the dispersant includes but is not limited to one or more of the group consisting of polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone, methyl cellulose, polyacrylic acid, sodium sulfosuccinate, sodium lauryl sulfate, sodium citrate and quaternary ammonium salts.
[0122] In a preferred embodiment, the preparation method provided by the present application further comprises: sequentially performing solid-liquid separation and freeze-drying treatment on the second product system to obtain a catalyst precursor. Performing solid-liquid separation on the second product system can separate the catalyst precursor from the second solvent, thereby obtaining a solid phase product; freeze-drying the solid phase product can remove the second solvent remaining in the solid phase product, and compared with other drying treatments, freeze-drying treatment is beneficial to inhibiting particle agglomeration caused by capillary adsorption effect.
[0123] In order to improve the separation efficiency of the catalyst precursor from water and the fourth solvent, preferably, the solid-liquid separation includes but is not limited to centrifugal separation.
[0124] In order to further improve the removal efficiency of residual water and the fourth solvent in the solid phase product and further inhibit the agglomeration of particles, preferably, the freeze-drying treatment temperature is -10°C to -60°C and the time is 6 to 24 hours.
[0125] In a preferred embodiment, the annealing treatment includes a stage heating treatment, including a first stage heat treatment, a second stage heat treatment, a third stage heat treatment and a fourth stage heat treatment performed in sequence. Compared with a single temperature condition heat treatment, the stage heating treatment is beneficial to improving the annealing effect, improving the yield of VN, and providing more active sites.
[0126] In a preferred embodiment, the first stage heat treatment includes: heating from 25°C to 300-350°C at a heating rate of 5-30°C / min, and keeping warm for 1-1.5 hours; the second stage heat treatment includes: continuing to heat to 600-650°C at a heating rate of 5-10°C / min, and keeping warm for 1-3 hours; the third stage heat treatment includes: continuing to heat to 800-900°C at a heating rate of 5-10°C / min, and keeping warm for 1-3 hours; the fourth stage heat treatment includes: continuing to heat to 1100-1200°C at a heating rate of 5-10°C / min, and keeping warm for 1-3 hours. During the first stage heat treatment, the free water is heated and volatilized, and the carrier precursor begins to thermally decompose. During the second stage heat treatment, V 2 O 5 A pre-reaction is carried out, during which the ammonium salt undergoes sufficient thermal decomposition, and the NH 3It can be used as a reducing agent at high temperature. At the same time, under the erosion and release of gas, it is beneficial to increase the specific surface area and porosity of the carrier. During the third stage of heat treatment, the thermally decomposed platinum salt decomposes into elemental Pt. During the fourth stage of heat treatment, the electronic structure between Pt and VN is adjusted, and the elemental Pt is transformed from a disordered structure to an ordered structure, thereby improving the electrocatalytic activity and durability of the supported catalyst.
[0127] In a preferred embodiment, the protective gas includes argon, nitrogen, helium and NH 3 One or more of the groups.
[0128] In a preferred embodiment, the second reducing agent is elemental carbon. Elemental carbon can convert V 2 O 5 Reduction to VN, thereby obtaining a VN vector.
[0129] In order to improve the reduction efficiency during the annealing treatment and thus improve the yield of the VN carrier, preferably, the weight ratio of the second reducing agent to the catalyst precursor is (0.1-0.5):1.
[0130] In order to better exert the reducing effect of the second reducing agent and thus improve the yield of the VN carrier, preferably, the average particle size of the second reducing agent is 50 to 1000 nm.
[0131] In a preferred embodiment, the annealing treatment is carried out in a tubular vacuum furnace, and the volume flow rate of the protective gas is 1 to 10 L / min. The introduction rate of the protective gas includes but is not limited to the above range, and limiting it within the above range is conducive to improving the annealing treatment effect, thereby helping to improve the catalytic activity and stability of the supported catalyst.
[0132] In a preferred embodiment, the preparation method provided in the present application further comprises: grinding the thermal reduction product after annealing to obtain a supported catalyst. Compared with not grinding, the supported catalyst obtained after grinding has a more uniform particle size and is convenient for use in hydrogen fuel cells.
[0133] The second aspect of the present application provides a supported catalyst, which includes a carrier and a noble metal; the supported catalyst is prepared by the preparation method of the supported catalyst provided by the present application. The noble metal in the supported catalyst provided by the present application is not easy to aggregate and migrate, and has good stability.
[0134] In order to improve the catalytic activity of the supported catalyst, in a preferred embodiment, the loading amount of the noble metal in the supported catalyst is 20 to 40 wt %.
[0135] The supported catalyst provided in the present application has a large specific surface area and can load more precious metals. In a preferred embodiment, the pore volume of the supported catalyst is 0.01 to 10.0 cm 3 / g, average pore size of 5-50nm, specific surface area of 450-600m 2 / g.
[0136] The third aspect of the present application provides a hydrogen fuel cell, including a catalyst, wherein the catalyst includes the above-mentioned supported catalyst provided in the present application. The noble metal in the supported catalyst provided in the present application is not easy to migrate and aggregate, has good stability, and is applied to a hydrogen fuel cell to increase its service life.
[0137] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0138] Example 1
[0139] A method for preparing a supported catalyst comprises:
[0140] (1) 20 g Na 3 VO 4 (CAS number is 13721-39-6, reagent pure, purity is 99%) and mixed with 200 mL of water to obtain a mixed system. The mass concentration of NaHCO is 50 g / L. 3 The aqueous solution was adjusted to pH 8.0 ± 0.5, stirred at 30 ° C and 300 rpm for 30 min, and filtered to remove trace impurities of aluminum, iron and calcium to obtain a solution containing Na 3 VO 4 Purified mother liquor;
[0141] (2) 0.175 mol of ammonium chloride was mixed with a mixed solvent of 50 mL of water and 50 mL of ethanol, and stirred at 300 rpm for 30 min to obtain an ammonium salt solution with a mass concentration of 93.6 g / L;
[0142] (3) adding 100 mL of the ammonium salt solution to 200 mL of the purified mother liquor at a rate of 10 mL / min to carry out a precipitation reaction. The temperature of the precipitation reaction is 25°C and the time is 60 min. After the reaction is completed, a first product system containing a carrier precursor is obtained, which is centrifuged, washed three times with anhydrous ethanol, and dried at 60°C for 12 h to obtain a carrier precursor.
[0143] (4) 5.75 g of the above-mentioned carrier precursor, 0.3 g of ammonium chloride, 0.42 g of chloroplatinic acid, 0.02 g of oxalic acid, 150 mL of water and 50 mL of ethylene glycol were mixed at 10° C. for 30 min to obtain a first mixed solution;
[0144] (5) 1.76 g of ascorbic acid was mixed with 0.2 g of polyacrylic acid and 100 mL of water to obtain 100 mL of 0.1 mol / L ascorbic acid solution (second mixed solution);
[0145] (6) adding 200 mL of the first mixed solution to 100 mL of the second mixed solution at a rate of 10 mL / min under stirring at 300 rpm to carry out a Pt salt phase transformation double decomposition reaction, and obtaining a second product system containing a catalyst precursor after reacting for 60 min, and then centrifugally separating, washing with anhydrous ethanol three times, and freeze-drying at -50 °C for 12 h to obtain a catalyst precursor;
[0146] (7) The catalyst precursor and carbon powder with an average particle size of 100 nm prepared as above were transferred to a tubular vacuum furnace for annealing treatment, nitrogen was introduced at a rate of 1 L / min, the temperature was increased from 25°C to 350°C at a heating rate of 15°C / min, the temperature was kept at that temperature for 1 h, the temperature was further increased to 650°C at a heating rate of 10°C / min, the temperature was kept at that temperature for 1 h, the temperature was further increased to 900°C at a heating rate of 5°C / min, the temperature was kept at that temperature for 1 h, the temperature was further increased to 1200°C at a heating rate of 5°C / min, the temperature was kept at that temperature for 3 h, and the temperature was naturally cooled to room temperature to obtain a supported catalyst. The supported catalyst has a carrier of VN, an active component of the precious metal Pt, and a loading amount of the precious metal of 20 wt%.
[0147] like Figure 1 and Figure 2 As shown, the noble metal Pt particles in the supported catalyst prepared in Example 1 are evenly distributed, and the average particle size of the Pt particles is 3.5 nm.
[0148] like Figure 3 As shown, at relative pressure P / P 0 When ≥0.45, the adsorption isotherm of the supported catalyst prepared in Example 1 has a hysteresis loop, which is consistent with the type IV isotherm curve type. The hysteresis loop is H3 type, which is caused by the capillary condensation phenomenon of the mesopores. This shows that the pores in the catalyst are mesopores and have good connectivity. and The calculated specific surface area of the catalyst is 565.09 m 2 / g, where P represents the pressure of the gas at adsorption equilibrium, P 0 represents the saturated vapor pressure of the adsorbate at the experimental temperature, V represents the volume of the adsorbed gas, Vm represents the monolayer adsorbed gas capacity, C represents a constant related to the adsorption heat and vaporization heat, and N A Avogadro's constant, A M represents the cross-sectional area of the adsorbed gas, V M Indicates the volume per gram molecule under standard conditions.
[0149] Depend on Figure 4 It can be seen that the pore size of the supported catalyst prepared in Example 1 is a bimodal distribution, with mesopores in the range of 4-5 nm and 5-50 nm respectively. Calculated by the BJH model, the pore volume and average pore size of the supported catalyst are 0.39 cm 3 / g, 14.21nm.
[0150] from Figure 5 It can be seen that the catalyst prepared in Example 1 exhibits similar hydrogen absorption-desorption peaks and Pt oxidation-reduction peaks as the commercial Pt / C catalyst. , it is calculated that Example 1 has a larger electrochemical active area ECSA = 108.09m 2 / g, where Q H represents the charge generated by hydrogen adsorption / desorption, and [Pt] represents the amount of platinum loaded on the working electrode. Figure 6 It can be seen that the half-wave potential E 1 / 2 The V is 0.829 V, which is significantly higher than that of commercial Pt / C catalyst (E 1 / 2 =0.63V), indicating that after annealing treatment, a high specific surface area oxygen reduction reaction electrocatalyst Pt / VN that is more suitable for oxygen reduction reaction is obtained.
[0151] Example 2
[0152] The difference from Example 1 is that in step (1), 20 g of Na-containing 3 VO 4 The raw materials (same as in Example 1) were dissolved in 200 mL of water to obtain a mixed system, and KHCO with a mass concentration of 50 g / L was used. 3 The aqueous solution was adjusted to pH 8.0 ± 0.5, stirred at 30 ° C and 300 rpm for 30 min, and filtered to remove trace impurities Fe, Ca and Al to obtain Na 3 VO 4 In step (7), a mixed gas of nitrogen and ammonia is introduced into the tubular vacuum furnace, and the volume ratio of nitrogen to ammonia is 3:1. The remaining steps are the same as those in Example 1.
[0153] Example 3
[0154] The difference from Example 1 is that the ethylene glycol in step (4) is replaced by an equal amount of water.
[0155] Example 4
[0156] The difference from Example 1 is that the mixing temperature in step (1) is 10° C. and the mixing time is 180 min.
[0157] Example 5
[0158] The difference from Example 1 is that the mixing temperature in step (1) is 95° C. and the mixing time is 5 min.
[0159] Example 6
[0160] The difference from Example 1 is that the mixing temperature in step (1) is 10°C.
[0161] Example 7
[0162] The difference from Example 1 is that: Na 3 VO 4 To remove impurities, in step (1), 20 g Na 3 VO 4 The mixed system obtained by mixing with 200 mL of water is used as the purified mother liquor for subsequent treatment steps.
[0163] Example 8
[0164] The difference from Example 1 is that the mass concentration of the ammonium salt solution in step (2) is 5.0 g / L.
[0165] Example 9
[0166] The difference from Example 1 is that the mass concentration of the ammonium salt solution in step (2) is 100.0 g / L.
[0167] Example 10
[0168] The difference from Example 1 is that the mass concentration of the ammonium salt solution in step (2) is 1.0 g / L.
[0169] Embodiment 11
[0170] The difference from Example 1 is that the dripping rate of the ammonium salt solution in step (3) is 30 mL / min.
[0171] Example 12
[0172] The difference from Example 1 is that the dripping rate of the ammonium salt solution in step (3) is 1 mL / min.
[0173] Embodiment 13
[0174] The difference from Example 1 is that the dripping rate of the ammonium salt solution in step (3) is 50 mL / min.
[0175] Embodiment 14
[0176] The difference from Example 1 is that the temperature of the precipitation reaction in step (3) is 20°C.
[0177] Embodiment 15
[0178] The difference from Example 1 is that the precipitation reaction temperature in step (3) is 80° C. and the time is 10 min.
[0179] Example 16
[0180] The difference from Example 1 is that the precipitation reaction time in step (3) is 90 minutes.
[0181] Embodiment 17
[0182] The difference from Example 1 is that the molar concentration of the second mixed solution in step (5) is changed so that the molar ratio of chloroplatinic acid to the first reducing agent ascorbic acid in step (6) is 0.001:0.5.
[0183] Embodiment 18
[0184] The difference from Example 1 is that the molar concentration of the second mixed solution in step (5) is changed so that the molar ratio of chloroplatinic acid to the first reducing agent ascorbic acid in step (6) is 0.1:0.005.
[0185] Embodiment 19
[0186] The difference from Example 1 is that the molar concentration of the second mixed solution in step (5) is changed so that the molar ratio of chloroplatinic acid to the first reducing agent ascorbic acid in step (6) is 0.1:0.0025.
[0187] Embodiment 20
[0188] The difference from Example 1 is that 0.85 g of sodium chloroplatinate is used to replace chloroplatinic acid in step (4) to obtain a first mixed solution.
[0189] Embodiment 21
[0190] The difference from Example 1 is that 0.4 g [Pt(acac) 2 ]Replace chloroplatinic acid in step (4) to obtain a first mixed solution.
[0191] Embodiment 22
[0192] The difference from Example 1 is that 0.65 g of platinum diamine dinitrite is used to replace chloroplatinic acid in step (4) to obtain a first mixed solution.
[0193] Embodiment 23
[0194] The difference from Example 1 is that the reaction time in step (6) is 10 min.
[0195] Embodiment 24
[0196] The difference from Example 1 is that the reaction time in step (6) is 5 min.
[0197] Embodiment 25
[0198] The difference from Example 1 is that in step (7), the temperature is increased from 25°C to 350°C at a heating rate of 5°C / min, kept at this temperature for 1 hour, then the temperature is further increased to 650°C at a heating rate of 5°C / min, kept at this temperature for 1 hour, then the temperature is further increased to 900°C at a heating rate of 5°C / min, kept at this temperature for 1 hour, then the temperature is further increased to 1200°C at a heating rate of 5°C / min, kept at this temperature for 3 hours, and then the temperature is naturally reduced to room temperature to obtain a supported catalyst.
[0199] Embodiment 26
[0200] The difference from Example 1 is that in step (7), the temperature is increased from 25°C to 350°C at a heating rate of 5°C / min, kept at this temperature for 1.5 h, then the temperature is further increased to 650°C at a heating rate of 5°C / min, kept at this temperature for 3 h, then the temperature is further increased to 900°C at a heating rate of 5°C / min, kept at this temperature for 3 h, then the temperature is further increased to 1200°C at a heating rate of 5°C / min, kept at this temperature for 1 h, and then the temperature is naturally reduced to room temperature to obtain a supported catalyst.
[0201] Embodiment 27
[0202] The difference from Example 1 is that in step (7), no staged temperature increase treatment is performed, and the temperature is increased from 25°C to 1200°C at a heating rate of 5°C / min, kept at that temperature for 3 hours, and then cooled naturally to room temperature to obtain a supported catalyst.
[0203] Comparative Example 1
[0204] The difference from Example 1 is that the Pt particles are loaded on the VN carrier by using the traditional impregnation deposition reduction method.
[0205] Comparative Example 2
[0206] The difference from Example 1 is that a commercial Pt / C catalyst (McLean P822267, platinum-carbon catalyst) is used, and the Pt loading in the catalyst is 20 wt %.
[0207] The specific surface areas of the supported catalysts prepared in all the above examples and comparative examples of the present application were tested by nitrogen adsorption-desorption method. The test results are shown in Table 1.
[0208] Table 1
[0209]
[0210] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0211] The open and porous structure enables the supported catalyst prepared in the present application to have a large specific surface area and rich pore structure, thereby exposing more active sites, which can not only effectively inhibit the aggregation, dissolution and Ostwald ripening of nano-Pt particles, but also increase the loading amount of active components. Its application in hydrogen fuel cells can improve the transmission and diffusion between reactants, catalytic centers and electrolytes, and improve the utilization rate of active metal atoms in the supported catalyst and the activity of electrocatalytic reactions.
[0212] Compared with the traditional deposition reduction method of first preparing a vanadium nitride (VN) carrier and then immersing it in a platinum salt compound solution for elemental platinum particle loading, the present application can be deposited in situ on the surface of the carrier precursor during the reduction of the precious metal compound, which can not only improve the atomic utilization of the active component (ie, the precious metal Pt) in the supported catalyst, but also improve the distribution uniformity of the precious metal on the support surface. The precious metal in the supported catalyst prepared by this method is not easy to migrate and aggregate, and the coordinated regulation of the interaction between the precious metal and the carrier in the supported catalyst can be achieved, so that the interaction between the precious metal and the carrier is stronger, and the precious metal can be effectively anchored, so that the stability of the prepared supported catalyst is better. Moreover, the above-mentioned preparation method of the present application requires less precious metal and higher atomic utilization. In addition, compared with the traditional impregnation deposition reduction method, the above-mentioned preparation method provided by the present application can well retain its morphology while changing the composition structure of the supported catalyst, so that it exposes more active sites.
[0213] During the annealing of the catalyst precursor, NH 3 On the one hand, the release of gas can form a porous structure, which can play a role in expanding the pores and increasing the specific surface area of the carrier, so that the supported catalyst can expose more catalytic active sites. Its application in hydrogen fuel cells can significantly improve the transport of reactants and products during the cathode oxygen reduction reaction and enhance mass transfer; on the other hand, under the action of the local micro-jet flow in the capillary pores of the carrier interface, the interaction energy between the precious metal particles is weakened, thereby effectively inhibiting the aggregation and migration of the precious metal particles.
[0214] In addition, the supported catalysts prepared by the phase separation method assisted by precious metal chelates have the following advantages: (1) Due to the good interaction between Pt and VN, the electronic structure at the coupling interface can be adjusted; (2) Reducing the particle size can provide more active sites; (3) The unique VN support porous network can not only improve the structural integrity and electrochemical durability, but also provide ultrafast electron / ion transfer channels.
[0215] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0216] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a supported catalyst, characterized in that: The preparation method of the supported catalyst comprises: Step S1, allowing vanadate and a first ammonium salt to undergo a precipitation reaction in a first solvent to obtain a first product system containing a carrier precursor; Step S2, reacting the carrier precursor, the second ammonium salt, the noble metal compound, the chelating agent, and the first reducing agent in a second solvent to obtain a second product system containing a catalyst precursor; Step S3, annealing the catalyst precursor and the second reducing agent in a protective gas to obtain the supported catalyst.
2. The method for preparing a supported catalyst according to claim 1, wherein The weight ratio of the vanadate, the first ammonium salt and the first solvent is (1-30): (0.01-10): (100-1500).
3. The method for preparing a supported catalyst according to claim 1 or 2, characterized in that: The vanadate is selected from one or more of the group consisting of sodium vanadate, potassium vanadate, calcium vanadate, sodium pyrovanadate, potassium pyrovanadate, calcium pyrovanadate, sodium metavanadate, potassium metavanadate and calcium metavanadate; and / or, the first ammonium salt is selected from one or more of the group consisting of ammonium chloride, ammonium sulfate, ammonium bisulfate, ammonium bicarbonate, ammonium carbonate, polydopamine, hexamethylenetetramine, melamine, ammonium polyacrylate and dopamine hydrochloride; and / or, the first solvent is a mixture of water and an organic solvent, and the organic solvent is selected from one or more of the group consisting of methanol, ethanol, propanol, ethylene glycol, isopropanol, polyacrylic acid, N,N-dimethylformamide, N,N-dimethylacetamide and diethylformamide.
4. The method for preparing a supported catalyst according to claim 3, characterized in that: The first solvent is a mixture of water and an organic solvent in a volume ratio of (50-1000):(5-500).
5. The method for preparing a supported catalyst according to claim 1, characterized in that: The step S1 comprises: Step S1-1, mixing a vanadate-containing raw material with water to obtain a mixed system, and adjusting the pH of the mixed system to 7.5-10.5 with an alkali solution to remove impurities, thereby obtaining a purified mother liquor containing the vanadate; Step S1-2, mixing the first ammonium salt and the first solvent to obtain an ammonium salt solution; Step S1-3, mixing the purified mother liquor with the ammonium salt solution and performing the precipitation reaction to obtain the first product system.
6. The method for preparing a supported catalyst according to claim 5, characterized in that: The alkali solution is selected from one or more of the group consisting of NaOH aqueous solution, Na2CO3 aqueous solution, NaHCO3 aqueous solution, KOH aqueous solution, K2CO3 aqueous solution, KHCO3 aqueous solution, and sodium acetate aqueous solution; and / or the mass concentration of the alkali solution is 5.0 to 100.0 g / L.
7. The method for preparing a supported catalyst according to claim 5, characterized in that: The mixing temperature in step S1-1 is 10-95°C and the mixing time is 5-180 min; and / or stirring is performed during the mixing process and the stirring speed is 300-500 rpm.
8. The method for preparing a supported catalyst according to claim 5, characterized in that: The mass concentration of the ammonium salt solution is 5.0 to 100.0 g / L.
9. The method for preparing a supported catalyst according to claim 5, characterized in that: In the step S1-3, the ammonium salt solution is dripped into the purified mother liquor at a dripping rate of 1 to 30 mL / min.
10. The method for preparing a supported catalyst according to claim 5 or 9, characterized in that: The volume ratio of the purified mother liquor to the ammonium salt solution is (2-5):1; and / or the temperature of the precipitation reaction is 20-80°C and the time is 10-60 minutes.
11. The method for preparing a supported catalyst according to claim 1, characterized in that: The preparation method further comprises: sequentially performing solid-liquid separation and drying on the first product system to obtain the carrier precursor.
12. The method for preparing a supported catalyst according to claim 11, characterized in that: The solid-liquid separation is selected from centrifugal separation; and / or the drying temperature is 50 to 90° C. and the drying time is 6 to 24 hours.
13. The method for preparing a supported catalyst according to claim 1, characterized in that: The weight ratio of the carrier precursor to the noble metal-containing compound is (1-20): (0.1-10); and / or, The weight ratio of the noble metal-containing compound to the chelating agent is (0.1-10): (0.001-15); and / or, The molar ratio of the noble metal-containing compound to the first reducing agent is (0.001-0.1): (0.005-0.5).
14. The method for preparing a supported catalyst according to claim 13, characterized in that: The noble metal-containing compound is a platinum salt compound, and the platinum salt compound is selected from one or more of the group consisting of chloroplatinic acid, chloroplatinate, [Pt(acac)2], diammine dinitrite platinum and [Pt(CH3NH2)4][PtCl4]; and / or, The chelating agent is selected from one or more of the group consisting of thiourea, sulfite, phosphoric acid, oxalic acid, arsenic acid, polyacrylic acid and polyvinyl alcohol; and / or, The first reducing agent is selected from one or more of the group consisting of elemental sulfur, ascorbic acid, sodium ascorbate, sodium citrate, formaldehyde, acetaldehyde, formic acid, acetic acid, hydrazine hydrate, metal borohydride salts, sulfites, ammonium chloride and oleylamine; and / or, The second solvent is selected from water and / or ethylene glycol.
15. The method for preparing a supported catalyst according to claim 1, characterized in that: The step S2 comprises: Step S2-1, mixing the carrier precursor, the second ammonium salt, the noble metal-containing compound, the chelating agent and a third solvent to obtain a first mixed solution; Step S2-2, mixing the first reducing agent, dispersing agent and fourth solvent to obtain a second mixed solution; Step S2-3, mixing the first mixed liquid and the second mixed liquid and performing the reaction to obtain the second product system.
16. The method for preparing a supported catalyst according to claim 15, characterized in that: The weight ratio of the carrier precursor, the noble metal-containing compound and the third solvent is (1-20): (0.1-10): (100-5000); and / or, The weight ratio of the carrier precursor to the second ammonium salt is (1-20): (0.001-15); and / or, In the second mixed liquid, the mass concentration of the dispersant is 1.0 to 5.0 g / L.
17. The method for preparing a supported catalyst according to claim 15 or 16, characterized in that: The second ammonium salt is selected from one or more of the group consisting of ammonium chloride, ammonium sulfate, ammonium bisulfate, ammonium bicarbonate, ammonium carbonate, polydopamine, ethylenediaminetetraacetic acid, ethylenediamine, triethylenetetramine, triethanolamine, hexamethylenetetramine, melamine, ammonium polyacrylate and dopamine hydrochloride; and / or, The third solvent is selected from water and / or ethylene glycol; and / or, The fourth solvent is selected from one or more of the group consisting of water, methanol, ethanol, propanol, ethylene glycol, isopropanol, N,N-dimethylformamide, N,N-dimethylacetamide and diethylformamide; and / or, The dispersant is selected from one or more of the group consisting of polyethylene glycol, polyvinyl alcohol, polyvinyl pyrrolidone, methyl cellulose, polyacrylic acid, sodium sulfosuccinate, sodium lauryl sulfate, sodium citrate and quaternary ammonium salts.
18. The method for preparing a supported catalyst according to claim 17, characterized in that: The second ammonium salt is of the same type as the first ammonium salt.
19. The method for preparing a supported catalyst according to claim 15, characterized in that: In the step S2-1, the mixing temperature is 0 to 150° C. and the mixing time is 30 to 180 min; and / or, In the step S2-2, the molar concentration of the first reducing agent in the second mixed solution is 0.01 to 10 mol / L; and / or, In the step S2-3, the first mixed solution is dripped into the second mixed solution at a rate of 1 to 10 mL / min. The mixing is carried out under stirring conditions at a speed of 300 to 500 rpm. The reaction time is 10 to 60 min.
20. The method for preparing a supported catalyst according to claim 1, characterized in that: The preparation method further comprises: sequentially performing solid-liquid separation and freeze-drying treatment on the second product system to obtain the catalyst precursor.
21. The method for preparing a supported catalyst according to claim 20, characterized in that: The solid-liquid separation is selected from centrifugal separation; and / or the freeze-drying treatment is performed at a temperature of -10°C to -60°C for 6 to 24 hours.
22. The method for preparing a supported catalyst according to claim 1, 5 or 15, characterized in that: The annealing treatment includes staged temperature increase treatment, including a first stage heat treatment, a second stage heat treatment, a third stage heat treatment and a fourth stage heat treatment performed in sequence; Among them, the first stage heat treatment includes: heating from 25°C to 300-350°C at a heating rate of 5-30°C / min, and keeping warm for 1-1.5 hours; the second stage heat treatment includes: continuing to heat up to 600-650°C at a heating rate of 5-10°C / min, and keeping warm for 1-3 hours; the third stage heat treatment includes: continuing to heat up to 800-900°C at a heating rate of 5-10°C / min, and keeping warm for 1-3 hours; the fourth stage heat treatment includes: continuing to heat up to 1100-1200°C at a heating rate of 5-10°C / min, and keeping warm for 1-3 hours.
23. The method for preparing a supported catalyst according to claim 22, characterized in that: The protective gas comprises one or more of the group consisting of argon, nitrogen, helium and NH3; and / or, The second reducing agent is elemental carbon; and / or, The annealing treatment is carried out in a tubular vacuum furnace, and the volume flow rate of the protective gas is 1 to 10 L / min; and / or, The preparation method further comprises: grinding the thermal reduction product after the annealing treatment to obtain the supported catalyst.
24. The method for preparing a supported catalyst according to claim 22, characterized in that: The weight ratio of the second reducing agent to the catalyst precursor is (0.1-0.5):1; and / or the average particle size of the second reducing agent is 50-1000 nm.
25. A supported catalyst, characterized in that The supported catalyst comprises a carrier and a noble metal; the supported catalyst is prepared by the supported catalyst preparation method according to claim 1.
26. The supported catalyst according to claim 25, characterized in that In the supported catalyst, the loading amount of the noble metal is 20 to 40 wt %; Preferably, the pore volume of the supported catalyst is 0.01 to 10.0 cm 3 / g, average pore size of 5-50nm, specific surface area of 450-600m 2 / g.
27. A hydrogen fuel cell comprising a catalyst, characterized in that: The catalyst comprises the supported catalyst according to claim 26.
Citation Information
Patent Citations
Platinum supported catalyst based on porous graphene / nano ceramic sandwiched structure and preparation method thereof
CN105833889A
Pd / VN hollow nanosphere electrocatalyst and preparation method and application thereof
CN109082676A
Method for preparing 2, 5-dimethylol tetrahydrofuran through reduction of vanadium-based catalyst electrocatalysis biomass compounds
CN109943863A
Preparation method of vanadium nitride loaded metal monatomic catalyst
CN117046498A
Preparation method of ZIF-8 loaded nano Au catalyst
CN117899940A
Cited By
Carbon-supported platinum-nickel catalyst as well as preparation method and application thereof
CN121097109A
Carbon supported platinum-nickel catalyst, its preparation method and application
CN121097109B
Supported catalyst and preparation method thereof
CN121972164A
Supported catalysts and methods for their preparation
CN121972164B